Implementasi Metode TOPSIS pada Penerima Bantuan Sosial Akibat Covid19 di Desa Kotabatu Ciomas Bogor - Alawiah, Enok Tuti; Putri, Dwi Andini (STIKOM Tunas Bangsa Pematangsiantar, 2021)
During the Covid 19 pandemic in 2020, many sectors were affected, one of which was the economic sector. Kotabatu Village, Ciobas District, Bogor Regency is a village that has been affected by social impacts due to the COVID-19 pandemic. Many people are forced to lose their jobs. Therefore, the Government provides cash social assistance. But the problem is that the provision of funds must be right on target only for the people who are affected. So that a decision support system is needed to determine the right policy. In this study, the TOPSIS method will be used as the best method for preference values and will be tested on 133 population samples. The results of the research conducted on the sample obtained a final score of 0.65, namely people who lost their jobs. So the provision of assistance can prioritize people who have lost their jobs in order to get help due to the COVID-19 pandemic